Reply to: Comments on “Walras–Bowley Lecture: Market Power and Wage Inequality” - Deb, Shubhdeep; Eeckhout, Jan; Patel, Aseem; Warren, Lawrence (Econometrica, 2024)
Census Bureau VIOLANTE (2023) AND VAN REENEN (2023) offer a comprehensive review of the lecture and point out the key aspects of the paper.We are grateful for their comments which have greatly improved this research.Our goals in this paper are twofold: (a) to provide a methodological framework that jointly incorporates goods market power (oligopoly) and labor market power (oligopsony) in a general equilibrium setting, and (b) to propose an empirical strategy for applying such a framework to microdata to estimate key structural parameters and a joint distribution of establishment-level productivity.Combined, these features allow us to quantify the relative importance of technological change and changes in market structure on the labor market, in particular on the evolution of wages, wage stagnation, and wage inequality.The main insight of our model is that market power and wage inequality are both endogenous objects, determined simultaneously in equilibrium by (1) the market structure (the number of competing firms); (2) the dispersion of establishment-level productivity; and (3) the substitutability parameters in the product and labor markets.We find that a change in the market structure (excluding changes in the dispersion of productivity and within-and between-market substitutability parameters) accounts for 8.1% of the rise in the skill premium, and 54.8% of the increase in between-establishment inequality.Our analysis also establishes that technology is indeed the main driver of wage inequality, whereas the decline in competition is behind the increasing gap between wages and productivity.Both commentators rightly point out that our assumption of perfectly overlapping boundaries between product and labor markets is strong.We agree, and nonetheless maintain this simplifying assumption for two reasons.The first is for computational tractability, as allowing for non-overlapping boundaries greatly increases the dimensionality of the system of equations needed to compute the economy's equilibrium. 1 Second, we es-